FACILITATING THE NEED FOR SELF-ESTEEM TO APPROACH THE ADOLESCENTS’ CHEMISTRY LEARNING STYLE - Simanjuntak, Familia Novita (PEOPLE: International Journal of Social Sciences, 2019)
Based on preliminary observation, it was found that one of the adolescents highest need in chemistry learning is self-esteem. Self-esteem affects the thinking process, desires emotions, values, and goals of an individual so that self-esteem for adolescents can be related to academic achievement. The adolescent’s target is middle adolescence. This adolescents learning style requires more warmth and more teacher-motivated. This study aims to support chemistry learning based on students’ need. One hundred and three (103) students were selected by purposive sampling technique. The students are 10th-grade students, Class of Natural Science X-1, X-2, & X-3 of The National High School 18 Jakarta. The needs of chemistry learning were observed as the preliminary observation using a Likert scale on Maslow’s hierarchy of needs. Then, the researcher composed a chemistry learning module, based on Likert scale analyze, with pre-test and post-test to measure the students’ learning outcomes which will be indicated as the learning style approach. Data analysis is a descriptive statistic and shows that there is an increase in the average value of chemistry learning outcomes. Means that self-esteem facilitating on chemistry learning process can be applied to approach the learning style of adolescents.